INOVASI DAN TANTANGAN DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN DI BALI - Primayani, Desi; Agus Wardana, Kadek (PARIWISATA BUDAYA: JURNAL ILMIAH PARIWISATA AGAMA DAN BUDAYA, 2025)
This article discusses the current state of tourism in Bali, with a focus on sustainable development strategies. Through secondary data analysis and interviews with stakeholders, this article aims to identify innovations and challenges in Bali's tourism industry. Tourism in Bali has become one of the main pillars of the regional economy, making significant contributions to the Gross Regional Domestic Product (GRDP) and creating jobs for the local community. However, the rapid growth of this sector also brings serious challenges related to sustainability. This paper discusses the impact of sustainable tourism in Bali, focusing on economic, socio-cultural, and environmental aspects. It is important for all stakeholders such as the government, local communities, and industry players to collaborate in creating a sustainable tourism model. Education about environmental awareness and cultural preservation must be an integral part of tourism development strategies. With the right approach, Bali can become a successful example of managing tourism sustainably, providing economic benefits while preserving its cultural heritage and natural environment.